Ecology of Syllidae (Annelida: Polychaeta) from shallow rocky environments in the Cantabrian Sea (South Bay of Biscay) - Alberto Serrano; Guillermo San Martín; Eduardo López (Scientia Marina, 2006)
The syllids inhabiting 12 hard bottom macrobenthic habitats were studied. A total of 38 species belonging to 19 genera were identified. Differences in density, species richness, and diversity among habitats were analysed, as well as the relationships between these ecological parameters and depth range, slope and in-bay/out-bay gradient. The effect of environmental variables on syllid distribution was studied using canonical ordination. A high faunistic homogeneity has been found, since all biotopes were dominated by a low number of eurytopic species (Syllis armillaris, S. gracilis and S. variegata). Habitat complexity, determined by physical disturbance, is the main structuring factor in syllid populations. Biotopes with the highest structural complexity displayed a high number of companion species increasing ecological indices and denoting a well-structured habitat. On the other hand, communities such as in upper intertidal habitats, mainly controlled by physical environmental variables, showed a poorer syllid fauna, dominated by ubiquitious species and a few stenotopic species well-adapted to those environments. However, this is not the case in some other intertidal biotopes, such as in Corallina, whose tangled structure prevents drying and provides shelter from predation, allowing a richer and more diverse syllid fauna.